In vitro antiprotozoal activity of some medicinal plants against sleeping sickness, Chagas disease and leishmaniasis. (4th December 2018) - Okba, Mona M; Sabry, Omar M; Matheeussen, An; Abdel-Sattar, Essam
Aim: Antiprotozoal activity of 36 medicinal plants was evaluated.Materials & methods: In vitro potency against Trypanosoma brucei brucei, T. b. rhodesiense, T. cruzi and Leishmania infantum beside cytotoxicity on MRC-5 fibroblasts were determined.Results & conclusion: Maytenus parviflora showed the highest activity against T. b. brucei (IC50 of 0.6 μg/ml) and T. b. rhodesiense (IC50 of 0.5 μg/ml) with low cytotoxicity (CC50 of 30 μg/ml). Saussurea costus and Commiphora wightii, showed pronounced potency against T. cruzi with an IC50 of 3.6 and 2.5 μg/ml, respectively. Jatropha pelargonifolia and Solanum villosum exhibited pronounced activity toward L. infantum with an IC50 of 3.2 and 2.0 μg/ml, respectively. M. parviflora, S. c ostus, C. wightii, J. pelargonifolia and S. villosum showed relevant selectivity.